2020
DOI: 10.1186/s40645-020-00372-w
|View full text |Cite
|
Sign up to set email alerts
|

Biogeophysical and biogeochemical impacts of land-use change simulated by MIROC-ES2L

Abstract: Land-use change is one of the focal processes in Earth system models because it has strong impacts on terrestrial biogeophysical and biogeochemical conditions. However, modeling land-use impacts is still challenging because of model complexity and uncertainty. This study examined the results of simulations of land-use change impacts by the Model for Interdisciplinary Research on Climate, Earth System version 2 for long-term simulations (MIROC-ES2L) conducted under the Land-Use Model Intercomparison Project pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Taking advantage of the characteristics of ESM to deal with forest dynamics, Ito and Hajima (2020) have shown that land use change due to human activities has a considerable impact on the runoff of soil moisture to rivers and vegetation biomass. Land use change deserves attention as a process that excites the interaction between human society and climate change.…”
mentioning
confidence: 99%
“…Taking advantage of the characteristics of ESM to deal with forest dynamics, Ito and Hajima (2020) have shown that land use change due to human activities has a considerable impact on the runoff of soil moisture to rivers and vegetation biomass. Land use change deserves attention as a process that excites the interaction between human society and climate change.…”
mentioning
confidence: 99%
“…The country's climate varies due to factors such as its location, atmospheric circulation and mountainous terrain, as well as the height and position of the mountains. Under conditions of increasing anthropogenic impact on nature, potential changes in the environment are manifested primarily in the biogeochemical processes of land cover [1]. Changes in climatic conditions have a profound effect on soil formation processes [2].…”
Section: Introductionmentioning
confidence: 99%
“…Forestation and deforestation affect the climate in two main ways (Ito & Hajima, 2020; Pongratz et al., 2010; Zhu et al., 2023). Firstly, by biogeochemical effects, that is, changes to the global carbon cycle and carbon storage pools that affect atmospheric CO 2 concentration and, therefore, the radiative absorption of the atmosphere.…”
Section: Introductionmentioning
confidence: 99%